National Identity of Young Adolescents of Czech and Bulgarian Origin - Z. Ganeva; M. Rasticova (University of Sofia, 2013)
The purpose of this study was to examine the structure of national identity among young adolescents of Bulgarian and Czech origin. University students (N=161) completed the Multigroup Ethnic Identity Measure-Revised (MEIM-R) (Phinney & Ong, 2007), four measures of psychological well-being and a measure of salience of ethnicity. Factor analyses of data for the two national groups yielded a two-factor structure that corresponded to two theoretical approaches to ethnic identity, as hypothesised. Similar patterns in magnitude of loadings were observed across groups, indicating that the MEIM-R could be used as a global composite index of national identity. National identity was related positively to measures of psychological well-being such as mastery, self-esteem and optimism, and negatively to measure of loneliness. MEIM-R scores were also moderately correlated with salience (the importance of a person's own national background in his or her life), across national groups.